DEVELOPMENT OF QUALITY RISK MITIGATION PLAN WITH SUPPLY CHAIN OPERATION MODEL APPROACHREFERENCE(SCOR) TO IMPROVE CRUDE PALM OIL PRODUCT QUALITY INPT CITRA SAWIT INDAH LESTARI - Maxmillianus Tarigan, Apul; Nasution, Harmein; Nazaruddin, Nazaruddin (CV. Radja Publika, 2022)
The quality of Crude Palm Oil (CPO) products is one of the indicators that producers need to fulfill so that the product is not rejected by consumers. In order to obtain good product quality, proper risk management is needed from suppliers to the Palm Oil Mill. In this case, the risk is from the quality of the fruit when it is harvested, the activities carried out after harvest, to the processing carried out at the Palm Oil Mill. Therefore, it is necessary to prepare a risk mitigation plan so that the quality of CPO products is maintained. Risk assessment is carried out using the SCOR and House of Risk model approaches in order to determine risk events, risk agents, and mitigation plans that need to be carried out so that the objectives can be achieved.